The first experience of using the "Senhance" robotic surgical system during cholecystectomy - M.A. Kashtalian; Ie.A. Kvasnevskyi; O.A. Kvasnevskyi (Medičnì Perspektivi)
The aim of our study was to evaluate the differences in intraoperative and postoperative outcomes of cholecystectomy using the Senhance robotic platform and laparoscopic cholecystectomy. A retrospective analysis of medical cases history of patients who underwent cholecystectomy from December 2021 to February 2022 was conducted. The treatment outcomes of patients with chronic calculous cholecystitis who underwent robotic cholecystectomy (RC) were compared with those who underwent laparoscopic cholecystectomy (LC). Robotic cholecystectomy was performed using the Senhance robotic platform. The RC and LC groups were matched for age, sex, body mass index and compared for the duration of the operation and hospital stay. For normally distributed data, the mean and standard deviation, determined using the Shapiro-Wilk test (p-value>0.05), were applied. Median and interquartile range (IQR) were also used. Difference between cohorts - 95% confidence interval (95% Confidence Interval) were estimated for normally distributed data. Data analysis was performed using standard summary statistics on the Jamovi 2.2.5 platform. Data were processed using application program packages. All surgical procedures were performed by two surgeons from Odesa National Medical University. Robotic cholecystectomy was performed on 18 patients and laparoscopic cholecystectomy was performed on 20 patients. There were no statistically significant differences between the groups in terms of length of hospital stay, blood loss or complications. There were no bile duct injuries, intraoperative complications, or conversions in either group. The only statistically significant difference was the total time under anesthesia (p>0.05), which was longer in the robotic cholecystectomy group. Cholecystectomy using the Senhance robotic platform was found to be safe, with an average operative time of 35.2±5.0 minutes, while the duration of laparoscopic cholecystectomy was 32.2±3.3 minutes. The study results showed that robotic cholecystectomy using the Senhance system is safe and effective. The use of robotic systems can improve precision and control during surgery, reduce blood loss and complications.